2016
DOI: 10.1523/eneuro.0112-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Ethanol or Nicotine Results in Increased Ethanol Self-Administration and Long-Term Depression in the Dorsolateral Striatum

Abstract: Ethanol (EtOH) and nicotine are the most widely coabused drugs. Tolerance to EtOH intoxication, including motor impairment, results in greater EtOH consumption and may result in a greater likelihood of addiction. Previous studies suggest that cross-tolerance between EtOH and nicotine may contribute to the abuse potential of these drugs. Here we demonstrate that repeated intermittent administration of either EtOH or nicotine in adult male Sprague Dawley rats results in tolerance to EtOH-induced motor impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 72 publications
1
14
0
2
Order By: Relevance
“…This finding is partially supported by previous studies, showing impaired eCB-LTD and reduced levels of the eCB arachidonoylethanolamide in the dorsal striatum following repeated administration of nicotine (Gonzalez et al 2002;Abburi et al 2016). Impaired eCB-LTD was not restored by TC-2F suggesting that this finding is not caused by enhanced FAAH activity, but rather linked to a reduced postsynaptic release of eCBs.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is partially supported by previous studies, showing impaired eCB-LTD and reduced levels of the eCB arachidonoylethanolamide in the dorsal striatum following repeated administration of nicotine (Gonzalez et al 2002;Abburi et al 2016). Impaired eCB-LTD was not restored by TC-2F suggesting that this finding is not caused by enhanced FAAH activity, but rather linked to a reduced postsynaptic release of eCBs.…”
Section: Discussionsupporting
confidence: 86%
“…A recent report (Abburi et al, 2016) observed reduced probability of release in mice given repeated nicotine injections. Though we observed a loss of presynaptic depression following HFS in the cNIC mice, at baseline we saw no difference in PPR (Figure 1a).…”
Section: Results Cnic Induces Ltp and Loss Of Presynaptic Ltd In Respmentioning
confidence: 94%
“…In a recent report, Abburi et al (2016) show that pretreatment with nicotine (1 × /day, 3 days) resulted in increased paired-pulse facilitation in striatopallidal MSNs of the DLS. They further show nicotine pretreatment blocked the ability of Win55-2-212 to induce presynaptic depression, suggesting that nicotine pretreatment induces a widespread presynaptic depression in striatopallidal MSNs.…”
Section: Discussionmentioning
confidence: 91%
“…MSN activity is driven by glutamatergic input from three distinct sources: cerebral cortex, thalamic nuclei, and cholinergic interneurons (CINs) that can co-release glutamate 9 11 . Drugs of abuse that affect glutamatergic input on to MSNs produce alterations in dorsal striatal-dependent behavior 12 17 .…”
Section: Introductionmentioning
confidence: 99%